Enriching Socioreligious Dynamics: A Macrostructural Analysis on Publications of the Indonesian Association for the Sociology of Religion (ASAGI) - Adib Sofia (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
Indonesian Association for the Sociology of Religion (ASAGI, abbrivated from Indonesian) accomodates 15 Study Programs of Sociology of Religion within the state Islamic universities of Indonesia. The association have had a deal in vision, mission, scientific development, curriculum design, compulsory courses and others. However, each of the fifteen study programs has its own scientific characteristics due to the differences from its history, background, and developmental direction. Academic journals, the output and the media that are directly related to the intellectual society, should be able to reveal the scientific characteristics of each institution. However, the characteristics is not necessarily easy to carry out. This writing reveals two premises, namely; First, differentiating each institution's idiosyncratical theme through its journal's macrostructure; Second, the suitability of discourses published by a ASAGI associated-journal with the identity and narative expectation of each institution concerned